Mobile app glossary of terms in Islamic banking and finance (Arabic-Malay-English) via iOS & android based devices - Dollah, Nafi@Hanafi; Mohd Feham, Mohd Ghalib; Hassan, Rusni; Omar, Zakaria; Zakaria, Abdul Wahab (2016)
The mobile terminology glossary app was designed by using a developmental research design using via rapid prototype instructional design model. The process begun with a need analysis conducted among 225 respondents in International Islamic University Malaysia (IIUM) It further explored the prototype development and its implementations for mobile accessibility by providing multilingual glossary of Islamic banking and finance terminologies (Malay-Arabic-English). This project the findings design and development prototype based on the need analysis stage, inclusive of mapping users’ device type, Internet accessibility, reasons for owning mobile devices, delivery and user interface, and preferred features to be embedded in the mobile app. Thus this project attempt to develop a prototype of a mobile app for glossary of terms in Islamic banking and finance since technology has already evaded our houses, dominated school children, and expanded across our professional lives. The main objective of this project is to embark on developing a mobile application for glossary term of Islamic banking and finance for the target community of academics and professionals using the step-by-step Rapid Prototype Model .